386 EFFECTS OF HYPERGLYCEMIA ON HEMATOPOIETIC STEM CELL TRANSPLANTATION. (10th December 2015) - Mosallaei-Benjamin, M.; Hamadani, M.; Holla, P.; Scofield, R. H.; Selby, G. B.
Abstract : Introduction: Studies of critically ill patients in various settings such as intensive care with mechanical ventilation, post MI, stroke and coronary bypass surgery have correlated tight glucose control with a substantial reduction in morbidity and mortality and length of hospital stay. To date the impact of hyperglycemia in the hematopoietic stem cell transplant (HSCT) population has not been studied. Objective: To investigate the relationship between hyperglycemia and morbidity and mortality in HSCT patients. Methods: Retrospective chart review of 98 consecutive adult patients (age > 17) admitted between January 1, 2002, and October 31, 2003, to University of Oklahoma Health Sciences Center Bone Marrow Transplant Unit was performed. Patients who received a myeloablative regimen and then underwent an autologous (n = 48) or allogeneic (n = 47) HSCT were analyzed in separate groups. Mean plasma glucose values during hospitalization for transplant were used to stratify the patients into euglycemic (glucose < 126 mg/dL) and hyperglycemic groups (glucose > 126 mg/dL). The primary outcome measure was length of inpatient stay defined as date of HSCT, designated day 0, until discharge. Secondary outcome measures were causes of inpatient morbidity. A tertiary outcome measure was in-hospital death. Results: Length of hospital stay for patients undergoing allogeneic HSCT was significantly longer (p = .02) in the hyperglycemic group (n = 26, mean 34.0 days) compared to the euglycemic group (n = 22, mean = 24.7 days). The hyperglycemic group also had significantly higher in-patient mortality (p = .0036), number of documented infections (p = .0015), and number of days on non-prophylactic antibiotics (p = .0078) compared to the euglycemic group. Length of hospital stay for patients undergoing autologous HSCT was also significantly longer (p = .01) in the hyperglycemic group (n = 29, mean = 31.33 days) versus the euglycemic group (n = 18, mean = 18.30 days). Hyperglycemic patients undergoing autologous HSCT also showed significantly higher number of documented infections (p = .028). Conclusion: This retrospective study indicates that hyperglycemia (blood glucose > 126 mg/dL) is strongly associated with increased mortality, morbidity and length of stay in patients undergoing HSCT. Randomized prospective studies are necessary to further elucidate the possible benefits strict glucose control may render in the setting of HSCT patients.